Lexical specification of tone in North Germanic - Lahiri, A; Wetterlin, A; Jönsson-Steiner, E (Cambridge University Press, 2005)
Accent 1 is very much accepted in the literature as the default tonal marker in Scandinavian languages. Consequently, stems and affixes are almost always specified for accent 2. Only rarely in some analyses is accent 1 specified for affixes, but never for stems. We believe that under these conditions, the resulting morphology/phonology interaction is rather complex, having to include special rules of accent marking, floating tones, deaccenting together with inexplicable exceptions. In our analysis of the tonal systems of Swedish and Norwegian, accent 1 is the lexically specified accent and accent 2 is postlexically assigned. Words and affixes may be lexically specified for accent 1, which inevitably dominates. Consequently, if a morphologically complex word includes a lexically specified affix or stem, the entire word with bear accent 1, giving us patterns of alternations like beskriva, skriva . This analysis enables us to account for all the facts almost exceptionlessly, with no special tonal rules, constraints or templates.